Design of cell permeable, fluorescent activity based probes for the lysosomal cysteine protease asparaginyl endopeptidase (AEP)/legumain - Sexton, Kelly B. (2006)
Asparaginyl endopeptidase (AEP), also known as legumain, is a cysteine protease that has been ascribed roles in antigen presentation yet its exact role in human biology remains poorly understood. We report here the use of a positional scanning combinatorial library of peptide AOMKs containing a P1 aspartic acid to probe the P2, P3 and P4 subsite specificity of endogenous legumain. Using inhibitor specificity profiles of cathepsin B and legumain, we designed fluorescent ABPs that are highly selective, cell permeable reagents for monitoring legumain activity in complex proteomes.